Aquisição bilíngue libras-português por uma criança CODA - Brancalione, Aline (2019)
The present research addresses the process of bilingual acquisition of Sign language / Portuguese by a CODA child, from the first months of life up to five years of age. The term CODA is an English acronym (Children of Deaf Adults). If the hearing children of deaf parents known as CODAs (Children of Deaf Adults) are correctly stimulated in their first years of life, they may become bilingual. In other words, they can acquire their parents’ language, a Sign Language, as the first language (L1), and the oral language of their country as the second language (L2). In order to reach the study goals, the research had a qualitative and participative approach, and used oral story and case study as methodologies. The author of this study is deaf and has two hearing children, CODAs. Oral story subsidized the construction of chapters two to thirteen, which followed a structured method: In item 1. Data on the development phases of CODA; Item 2. Theoretical approaches that dialogue with these data; Item 3. Analysis of the presented data. The theoretical research was based on Vygotsky and his collaborators’ theory, which presents studies about human and language development, as well as other renowned authors in the area of Deafness studies. The study also presents photographic and image records aimed at demonstrating, in a visual way, the acquisition of the two languages by the research participant. The analysis showed that CODA, with the frequent use of stimuli by the parents, naturally acquired the Brazilian Sign Language as first language (L1) and the Portuguese language as second language (L2), reaching five years of age with the ability to communicate in Brazilian Sign Language and in Portuguese, with strong bilingual and bicultural characteristics. Therefore, the research process allowed the construction of deeper knowledge about the bilingual acquisition of CODAs and can significantly contribute to the Brazilian deaf community and researchers in the area, since studies on this minority group are still incipient in Brazil.